Farmer Education Development under the Perspective of Migrant Workers’ Intergenerational Mobility - Fan, Rong (EDP Sciences, 2018)
This paper argues the appearances of at least three generations’ replacement of migrant workers since the reform and open policy, which is the first generation, the new generation and the third generation. Under the condition of disparate family and social circumstances, the migrant workers are no longer the abstract groups with the same degree of homogeneity. The public tendency is more clearly in the aspect of mobility motivations, city identity and self-identity, employment industry, education and skills training. Therefore, the importance of migrant workers education highlights increasingly. According to the analysis of social development and migrant workers’ self-development, we need to develop farmer education. But the present situation of farmer education is misfit. So we need to put forward the countermeasures and suggestions on peasants’ compulsory education, vocational training institutions, and amateur cultural education.